Cryptocurrencies: technology, initiatives of banks and central banks, and regulatory challenges - Carvalho, Carlos Eduardo (2021)
This paper analyses the impacts of the innovation known as distributed ledger technology (DLT) on the monetary system and on financial activities. Private cryptocurrencies, such as Bitcoin, are permissionless means of payment, based on blockchain, a form of DLT. Evaluations suggested that these private cryptocurrencies could compete with the banks payment systems and even supplant state currency. The development of these technologies has the potential to modify profoundly monetary and financial practices, but there are no indications that they may threaten the centrality of state money and the banking system in the contemporary monetary order. Major international banks have developed cryptocurrencies for settlement systems and for interbank transactions, including the so-called stablecoins, issued by highly technological companies with on par conversion into state money. Some central banks are studying the launch of state cryptocurrencies that could coexist with their fiduciary state currency and even replace their paper currency. The use of this technology results in new challenges for regulation, including the fact that cryptocurrencies can be used for money laundering and by organized crime.